2013
DOI: 10.1089/chi.2012.0138
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Quality of Meals Compared to Snacks in Child Care

Abstract: Background: Most young children are in child care. Previous studies suggest that children may receive insufficient vegetables, and foods and beverages with added sugars, fats, and sodium in these settings. None have compared the nutritional quality of meals to snacks.Methods: Directors from 258 full-day child-care centers in two urban counties of southwestern Ohio were surveyed via telephone in the fall of 2009 about their nutrition practices, and asked to provide a current menu. Lunch and afternoon snack menu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
26
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 32 publications
5
26
0
2
Order By: Relevance
“…Little is known about the potential mechanisms linking child care with obesity, if such a relationship exists. The nutrition environment at child care may be an important mechanism to explore given recent studies in the US, the UK, and the Netherlands that highlight the nutritional inadequacy of foods and beverages commonly served to children in child care; specifically, meals and snacks lack sufficient fruits, vegetables, and whole grains and include excessive fats and sugars (Copeland, Benjamin Neelon, Howald, & Wosje, 2013; Frampton et al, 2014; Gubbels et al, 2014, 2015; Maalouf, Evers, Griffin, & Lyn, 2013; Neelon et al, 2015; Parker, LloydWilliams, Weston, Macklin, & McFadden, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Little is known about the potential mechanisms linking child care with obesity, if such a relationship exists. The nutrition environment at child care may be an important mechanism to explore given recent studies in the US, the UK, and the Netherlands that highlight the nutritional inadequacy of foods and beverages commonly served to children in child care; specifically, meals and snacks lack sufficient fruits, vegetables, and whole grains and include excessive fats and sugars (Copeland, Benjamin Neelon, Howald, & Wosje, 2013; Frampton et al, 2014; Gubbels et al, 2014, 2015; Maalouf, Evers, Griffin, & Lyn, 2013; Neelon et al, 2015; Parker, LloydWilliams, Weston, Macklin, & McFadden, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…United States benchmarks for nutrition have suggested that half to two-thirds of children's nutritional needs should be met while in childcare (Benjamin Neelon et al, 2011). However, many preschoolers consume low amounts of vegetables and fruit, and excessive amounts of saturated fat and added sugars while in childcare centers (Ball et al, 2008;Copeland et al, 2013;Erinosho et al, 2013;Gubbels et al, 2014). Furthermore, despite opportunities for children to be active inside and outside, studies have consistently shown that sedentary time within childcare centers is typically high, while physical activity levels are typically very low, accumulating less than 20 minutes per day of moderate-to-vigorous physical activity (MVPA) during an 8-hour day (Kuzik et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…32 This is important because growing evidence suggests that the child-care environment can influence positive and negative dietary behaviors in young children. [33][34][35][36][37] Therefore, beginning to explore how the child-care food environment might influence the home feeding environment is of importance.…”
Section: Introductionmentioning
confidence: 99%